Bimetal-Organic Framework: One-Step Homogenous Formation and its Derived Mesoporous Ternary Metal Oxide Nanorod for High-Capacity, High-Rate, and Long-Cycle-Life Lithium Storage - Li, Hao; Liang, Ming; Sun, Weiwei; Wang, Yong (Advanced functional materials, 2016)
Metal–organic frameworks (MOFs) and relative structures with uniform micro/mesoporous structures have shown important applications in various fields. This paper reports the synthesis of unprecedented mesoporous NixCo3−xO4 nanorods with tuned composition from the Co/Ni bimetallic MOF precursor. The Co/Ni‐MOFs are prepared by a one‐step facile microwave‐assisted solvothermal method rather than surface metallic cation exchange on the preformed one‐metal MOF template, therefore displaying very uniform distribution of two species and high structural integrity. The obtained mesoporous Ni0.3Co2.7O4 nanorod delivers a larger‐than‐theoretical reversible capacity of 1410 mAh g−1 after 200 repetitive cycles at a small current of 100 mA g−1 with an excellent high‐rate capability for lithium‐ion batteries. Large reversible capacities of 812 and 656 mAh g−1 can also be retained after 500 cycles at large currents of 2 and 5 A g−1, respectively. These outstanding electrochemical performances of the ternary metal oxide have been mainly attributed to its interconnected nanoparticle‐integrated mesoporous nanorod structure and the synergistic effect of two active metal oxide components. Microwave‐assisted one‐step formation of bimetallic Co/Ni‐metal–organic framework‐74 is used to fabricate a mesoporous Co–Ni–O nanorod, which delivers higher‐than‐theoretical reversible capacities, with excellent high‐rate performances for lithium‐ion batteries.